The effectiveness of Road Safety Audit in Malaysia: a systematic review / Raja Nurulhaiza Raja Nhari ... [et al.] - Raja Nhari, Raja Nurulhaiza; Mohamed, Azman; Selamat, N.Ainaa; LB, Tan; A. Zawawi, M. Fadzly (2022)
The Road Safety Audit (RSA) is an existing road infrastructure tool used to prevent or reduce the severity of injuries and the RSA safety principles are applied in road design and road improvement. Few comparative reviews have been carried out on the implementation of RSA in other countries. The present article was carried out to analyse the existing literature on RSA practices by summarizing the best available international evidence on the effectiveness of the RSA. Guided by the PRISMA Statement (Preferred Reporting Items for Systematic reviews and Meta-Analyses) review method was conducted, a systematic review of the Scopus and Science Direct databases identified 16 related studies. Further review of these articles resulted in four main themes – RSA Practices, Road Safety Toolkit, Road Safety Auditor, and Issues in implementation of RSA. There are some suggestions for potential research proposed in the study. More qualitative studies are required because the RSA activities in Malaysia provide in-depth analysis and thorough explanations. In addition to direct analysis synthesis in the sense of RSA activities, the study requires unique and normal systematic review approaches and needs to practice complementary search strategies such as citation tracking, contacting experts, reference searching and snowballing. Finally, after this study, a set of suggestions was provided for future academics' consideration.